2013
DOI: 10.1093/jeg/lbt030
|View full text |Cite
|
Sign up to set email alerts
|

Geography and High-Tech Employment Growth in US Counties‡

Abstract: Abstract. This paper investigates the role of geography in high-tech employment growth across U.S. counties. The geographic dimensions examined include industry cluster effects, urbanization effects, proximity to a research university, and proximity in the urban hierarchy. Growth is assessed for overall high-tech employment and for employment in various high-tech sub-sectors. Econometric analyses are conducted separately for samples of metropolitan and nonmetropolitan counties. Among our primary findings, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 71 publications
2
47
0
Order By: Relevance
“…(EMSI) with information on county employment and earnings disaggregated at 4--digit NAICS level. EMSI data have been successfully used in various studies in recent years (Betz et al, 2015;Dorfman et al, 2011;Fallah et al, 2011;Fallah et al, 2014;Nolan et al, 2011). This allows us to measure oil--and gas--extraction employment, as well as other sectors of interest, more precisely (especially in calculating our energy and industry mix terms).…”
Section: Estimation Approach Variables and Data Sourcesmentioning
confidence: 99%
“…(EMSI) with information on county employment and earnings disaggregated at 4--digit NAICS level. EMSI data have been successfully used in various studies in recent years (Betz et al, 2015;Dorfman et al, 2011;Fallah et al, 2011;Fallah et al, 2014;Nolan et al, 2011). This allows us to measure oil--and gas--extraction employment, as well as other sectors of interest, more precisely (especially in calculating our energy and industry mix terms).…”
Section: Estimation Approach Variables and Data Sourcesmentioning
confidence: 99%
“…The economic geography of these industries has been the subject of considerable research (Currid & Connolly, 2008), with the importance of tacit knowledge and the need to hire workers with highly specific and often unique skills meaning that firms in the high-tech sector tend to concentrate spatially in a limited number of cities (Bieri, 2010;Fallah et al, 2014). These are factors which have been known in academic and policy circles for some time and have triggered a race to create and attract high-tech firms as the formula for achieving local economic development and economic success.…”
Section: High-technology Growth and Povertymentioning
confidence: 99%
“…Knowledge spillovers may be particularly important in urban environments in the case of high-tech industries (Fallah et al, 2014). Echeverri-Carroll and Ayala (2009), in particular, have indicated that there is an overall 'tech-city wage premium' in cities with high shares of tech-employment.…”
Section: High-technology Growth and Povertymentioning
confidence: 99%
See 1 more Smart Citation
“…One might easily expect that there exist spatial differences because the economic activities are unevenly distributed. Building on this idea, many studies have shown that there exists a meaningful correlation between a firm's location and job creation (Act et al 2007;Loof and Nabavi 2013;Feser et al 2008;Fallah et al 2014;Kim et al 2013).…”
Section: Smes' Basic Factors and Job Creationmentioning
confidence: 99%